2013
DOI: 10.3390/molecules181215398
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib Congeners Induce Apoptosis of Hepatocellular Carcinoma via CIP2A Inhibition

Abstract: CIP2A is an oncoprotein that upregulates p-Akt and promotes cancer cell proliferation and survival. The proteasome inhibitor bortezomib has been shown to reduce CIP2A and lead to cell apoptosis. Here; we modified the functional group of bortezomib to generate a series of novel compounds and conducted a structure-activity relationship (SAR) study. The results showed that compound 1 was able to repress CIP2A expression and cell apoptosis in the same manner as bortezomib, but with less potency in inhibition of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…First, cancer cells which exhibited equal proteasomal inhibition displayed a differential apoptotic response to Bortezomib (Chen et al, 2008; Liu et al, 2013; Tseng et al, 2012). Second, Bortezomib derivatives with diminished proteasomal inhibition showed equal or increased cytotoxicity to cancer cells (Hou et al, 2013). Additional evidence suggested that this secondary mechanism of action was through a loss of CIP2A expression in multiple cancer types (hepatocellular carcinoma, head and neck squamous cell carcinoma, triple negative breast cancer, and a variety of leukemias), resulting in increased PP2A activity (Chen et al, 2010; Ding et al, 2014; Hou et al, 2013; Lin et al, 2012; Liu et al, 2013) (Figure 3A).…”
Section: Targeting the Pp2a Inhibitor Cip2amentioning
confidence: 99%
See 1 more Smart Citation
“…First, cancer cells which exhibited equal proteasomal inhibition displayed a differential apoptotic response to Bortezomib (Chen et al, 2008; Liu et al, 2013; Tseng et al, 2012). Second, Bortezomib derivatives with diminished proteasomal inhibition showed equal or increased cytotoxicity to cancer cells (Hou et al, 2013). Additional evidence suggested that this secondary mechanism of action was through a loss of CIP2A expression in multiple cancer types (hepatocellular carcinoma, head and neck squamous cell carcinoma, triple negative breast cancer, and a variety of leukemias), resulting in increased PP2A activity (Chen et al, 2010; Ding et al, 2014; Hou et al, 2013; Lin et al, 2012; Liu et al, 2013) (Figure 3A).…”
Section: Targeting the Pp2a Inhibitor Cip2amentioning
confidence: 99%
“…Second, Bortezomib derivatives with diminished proteasomal inhibition showed equal or increased cytotoxicity to cancer cells (Hou et al, 2013). Additional evidence suggested that this secondary mechanism of action was through a loss of CIP2A expression in multiple cancer types (hepatocellular carcinoma, head and neck squamous cell carcinoma, triple negative breast cancer, and a variety of leukemias), resulting in increased PP2A activity (Chen et al, 2010; Ding et al, 2014; Hou et al, 2013; Lin et al, 2012; Liu et al, 2013) (Figure 3A). Furthermore, Bortezomib’s cytotoxic function was blunted by siRNA mediated loss of PP2A-C subunit, supporting the role of PP2A in mediating Bortezomib-induced cytotoxicity (Lin et al, 2012).…”
Section: Targeting the Pp2a Inhibitor Cip2amentioning
confidence: 99%
“…The antitumor activity of Bortezomib has been reported in a variety of human cancers with several described molecular mechanisms . Independent investigations have now identified CIP2A as a Bortezomib target in HCC, leukemias, head and neck squamous cell carcinomas (HNSCC), triple negative breast carcinomas and colon cancers . CIP2A expression has been suggested to be the major determinant for mediating Bortezomib induced apoptosis in these cancers.…”
Section: Role Of Cip2a As a Biomarker For Anticancer Drugsmentioning
confidence: 99%
“…CIP2A gene polymorphisms and hepatocellular carcinoma susceptibility has been reported [ 73 ]. Bortezomib (a proteosome inhibitor used in clinics on myeloma patients) congeners induced apoptosis in hepatocellular carcinoma cells via CIP2A inhibition [ 90 ]. The inhibition of CIP2A has been shown to determine the effect of bortezomib on apoptosis and PP2A-dependent AKT inactivation in hepatocellular carcinoma indicating that CIP2A may be a biomarker for predicting clinical response of bortezomib in hepatocellular carcinoma treatment [ 91 ].…”
Section: Introductionmentioning
confidence: 99%